A serological survey on bulls of an artificial insemination centre for infectious bovine rhinotracheitis (IBR) virus neutralising antibodies - ΠΑΠΠΟΥΣ Χ.; ΔΗΜΗΤΡΙΑΔΗΣ Ι.; ΠΟΙΛΑΣ Σ.; ΚΑΡΑΤΖΑΣ Γ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The results of periodical serological examinations of bulls in an Artificial Insemination Centre for antibodies neutralising IBR virus, during the period 1978-81 are given. 155 serum samples belonging to 45 animals of this centre were tested. 29 sera were found positive (18.9%) coming from 13 animals. The percentage by year of the IBR infection varied from 14.8 to 25%. Except one clinical case of IBR the other positive animal did not show apparent disease.